Optimization of negative capacitance junctionless gate-all-around field-effect transistor using asymmetric non-local lateral Gaussian doping. (May 2023) - Han, Ying; Lü, Weifeng; Wei, Weijie; Zhang, Caiyun; Chen, Dengke
Abstract: Technology advancements directed towards Internet-of-Things (IoT) and wearable computing electronics applications are booming in low-power devices, which requires downscaling of power supply voltage without sacrificing the performance of the device. A negative capacitance junctionless gate-all-around field-effect transistor (NC-JL-GAAFET) is investigated using technology computer-aided design (TCAD) simulations to further suppress the short-channel effects and reduce power consumption. Lateral Gaussian doping (LGD), proposed for the NC-JL-GAAFET, is considered its main doping mode. An asymmetric structure with varying lengths of source/drain extension regions is introduced into non-local LGD NC-JL-GAAFET. The results reveal that the proposed device with a larger length ratio for drain extension region has a higher switching current ratio and lower subthreshold swing. Furthermore, the TCAD simulations validate that the electrical characteristics can be easily optimized by adjusting the ferroelectric (FE) layer thickness on the gate stack. Therefore, an asymmetric non-local LGD NC-JL-GAAFET provides a potential scaling solution for the next-generation low-power devices.